Inbreeding marriage related to stunting in children aged 24-59 months - Ummi Kalsum; Krista Julita; Diah Restu Pertiwi (Poltekkes Kemenkes Yogyakarta, 2019)
Stunting is a nutritional problem that often occurs in toddlers in Indonesia, as well as in Jambi. Kerinci is the highest incidence of stunting among regencies in Jambi. Inbreeding marriages are common in Kerinci Regency compared to other regencies. This study aimed to analyze the relationship of inbreeding marriage and other factors to the occurrence of stunting in Semurup Kerinci Regency, Jambi. This study was a cross-sectional design. Population studies were under-five children aged 24-59 months. The sampling technique was multistage random by the number of samples as much as 158 calculated by sample size determination in health studies from WHO. Primary data collection in March-April 2019. Research variables were inbreeding marriage, father’s height, mother’s height, father’s education, mother’s education, mother’s knowledge, mother’s job, family size and family socio-economic. Data collected by interviews and height measurements. Data analysis used Chi-square and Multiple Logistic Regression. The proportion of stunting was 57.6% and inbreeding marriage was 42.4%. There were a significant relationship between inbreeding marriage (Prevalence Ratio (PR) = 1.81; 95% CI = 1,38-2,37; P = 0,000); father’s height (PR = 1.49; 95% CI = 1.09-2.04; P = 0.010) and mother’s height (PR = 2.54; 95% CI = 1,78-3,62; P = 0,000) to the occurrence of stunting. The dominant factor was inbreeding marriage (PR= 3,45; 95% CI = 1,60-7,45; P = 0,002) after controlling by mother’s height and mother’s knowledge. The conclusion is inbreeding marriage of parent related to stunting in children.